Experiences of academic practice in primary health care: challenges of systematized nursing consultation (Research, Society and Development, 2021)
Objective: to report the experience of academic and extension practice of undergraduate nursing students in systematized care during nursing consultations with hypertensive and/or diabetic users in primary health care. Methodology: descriptive study of the experience report type, which was developed from the experience during the practice of academics and extension scholarship holders of the sixth and eighth period of the Undergraduate Nursing course. Systematized care in nursing consultations, with hypertensive and diabetic users, was developed from March 2019 to January 2020 in a primary health care unit. Results: the systematization of nursing care allows for the management of the care process, by enabling the operationalization of the nursing consultation, which, in addition to valuing professional practice, favors an intervention approach with users assisted by academics. This approach provides the opportunity to integrate theoretical teaching with care practices and promotes the appreciation of the human being, through the offer of unique, holistic and multidimensional care at the beginning of professional training. Final Considerations: systematized care practice in primary care exceeded the expectations of academics, teachers and the multidisciplinary team that works in care, as it increased the adherence of users to outpatient consultations and educational meetings, in addition to improving their quality of life and adopting a healthier lifestyle.